2017
DOI: 10.1007/s00508-017-1266-z
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of quality of life and psychological distress after inpatient cancer rehabilitation

Abstract: Summary Background With the growing number of cancer survivors worldwide the need for high quality cancer rehabilitation after primary treatment is steadily increasing. The aim of the present study was to investigate change of psychological distress and health-related quality of life (HRQOL) during multidisciplinary inpatient cancer rehabilitation in a large sample of cancer survivors suffering from different cancer entities. Methods We analyzed data from r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…This data is not documented in a standardized fashion but rather paraphrased by the physicians. Several reports have previously described improvement of various components of HRQOL by inpatient or outpatient cancer rehabilitation [21][22][23][24][25]42]. Many investigations focus on patients from certain cancer entities, such as breast [21,22,42], bladder [43], or prostate cancer [44].…”
Section: Discussionmentioning
confidence: 99%
“…This data is not documented in a standardized fashion but rather paraphrased by the physicians. Several reports have previously described improvement of various components of HRQOL by inpatient or outpatient cancer rehabilitation [21][22][23][24][25]42]. Many investigations focus on patients from certain cancer entities, such as breast [21,22,42], bladder [43], or prostate cancer [44].…”
Section: Discussionmentioning
confidence: 99%
“…Several aspects need to be considered as to why the integrated nurse‐led CIM approach reported here did not demonstrate QoL benefits in patients completing CHT. CHT is the most burdensome treatment phase for cancer patients, and oncological rehabilitation studies report that patients’ QoL needs almost a month to recover after primary treatment . This might be a possible explanation for not having found an effect shortly after the end of CHT.…”
Section: Discussionmentioning
confidence: 99%
“…CHT is the most burdensome treatment phase for cancer patients, 2 and oncological rehabilitation studies report that patients' QoL needs almost a month to recover after primary treatment. 38 This might be a possible explanation for not having found an effect shortly after the end of CHT. So, it can be hypothesized that the positive effect needs time to develop.…”
Section: Discussionmentioning
confidence: 99%
“…Inpatient rehabilitation services play a significant role in overall QOL improvement and affect many patients' ability to cope with their disabilities. 7,8 Previous studies have reported that cancer patients benefit from inpatient rehabilitations. [1][2][3][4] However, functional impairments related to cancer are often not referred for specialized rehabilitation services as the main focus of oncologists remains the treatment of the disease rather than the functional deficits it causes.…”
mentioning
confidence: 99%